Semantic Connection between the Sound of the Comma (fasila) and Verse in which it is Separated - Muhammad Amin Abdullah Al-Imam, Obaida Luqman (Journal of Tikrit University for Humanities, 2025)
Knowing the characteristics of the sounds and linking them to the semantics is one of the important matters which help us to reach to the meaning of the text to be studied. The Holy Qur’an is an inexhaustible source for researchers. In this research, it is found that there is a connection between the existing of a comma and the verse (Aya) it is separated. The Quranic fasila (comma) has a great role in enhancing the meaning of the Quranic verse. Therefore the researcher is introducing and listing the verses of bless (naeem) and to take samples of each comma showing the sounds of these commas and relating them to the text.